EFEKTIVITAS PROMOSI PARIWISATA MELALUI CERITA BARU CENTER (CBC) DI BANDAR UDARA INTERNASIONAL SULTAN SYARIF KASIM II - Oktaviani, Claudia; Arief, Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of conducting this research is to know the effectiveness of tourism promotion through Cerita Baru Center (CBC) at Sultan Syarif Kasim II International Airport.This research uses descriptive quantitative methode to analyze the problems. The population of this research are foreign tourist through the International Arrival of Sultan Syarif Kasim II International Airport. The sampel of this research was 50 respondents, and its taking by Accidental Sampling tecnique based on convinience. And for measuring the effectiveness of tourism promotion through Cerita Baru Center (CBC) at Sultan Syarif Kasim II International Airport are four dimensions they are Empathy, Persuation, Impact and Communication.Based on the research that has been conducted, respondents agree with four dimensions effectiveness of promotion tourism get results agree, tourist give a very good response and the dominant dimensions is Communication.Keywords: The Effectiveness Of Tourism Promotion, Cerita Baru Center (CBC)